The complete guide to kitchens : do-it-yourself and save, design & planning, quick updates, custom cabinetry, remodeling projects on budget.: do-it-yourself and save, design & planning, quick updates, custom cabinetry, remodeling projects on budget. (©2009) - Unknown
No abstract available